2017
DOI: 10.3899/jrheum.161068
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Eicosapentaenoic Acid Are Associated with Anti-TNF Responsiveness in Rheumatoid Arthritis and Inhibit the Etanercept-driven Rise in Th17 Cell Differentiationin Vitro

Abstract: ObjectiveTo determine whether levels of plasma n-3 PUFAs are associated with response to anti-TNF agents in RA, and whether this putative effect may have its basis in altering anti-TNF driven Th17 cell differentiation MethodsPlasma was collected at baseline and after three months of anti-TNF treatment in ResultsPlasma PC EPA levels, and the EPA/arachidonic acid ratio, correlated inversely with change in DAS28 scores at 3 months (-0.51; p=0.007, and -0.48; p=0.01 respectively), indicating that higher plasma EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
0
16
1
Order By: Relevance
“…This was thought to be reverse causation, with a metabolic state in RA driving increased desaturase enzyme activity for which LA is a substrate. Indeed, we have previously suggested that D5D activity may be reduced following treatment with anti-TNF 38. In this cohort we did not find D5D or D6D product to precursor ratios to be associated with risk of RA, or to vary with time to diagnosis, but we did observe a non-statistically significant trend for lower LA levels in subjects closest in time to RA diagnosis.…”
Section: Discussioncontrasting
confidence: 72%
“…This was thought to be reverse causation, with a metabolic state in RA driving increased desaturase enzyme activity for which LA is a substrate. Indeed, we have previously suggested that D5D activity may be reduced following treatment with anti-TNF 38. In this cohort we did not find D5D or D6D product to precursor ratios to be associated with risk of RA, or to vary with time to diagnosis, but we did observe a non-statistically significant trend for lower LA levels in subjects closest in time to RA diagnosis.…”
Section: Discussioncontrasting
confidence: 72%
“…Additionally, a relationship between serum EPA levels and good treatment response, as defined by EULAR, was found ( p = 0.02). It may be explained by the fact that while Th17 stimulation was found both to be exaggerated by etanercept in vitro and also to be present in patients with a poor treatment response, EPA intake seems to prevent it [ 21 ].…”
Section: The Beneficial Role Of N-3 Pufas In Rheumatoid Arthritismentioning
confidence: 99%
“…It improved also the remission when associated to conventional disease-modifying DMARDs [98]. In addition, the concentration of EPA in serum was associated with a better response to anti-TNF therapy [99]. Taken together, these results suggested that omega 3 FA have a favorable effect on inflammation and pain in RA, that can be, at least partially, explained by the generation of omega 3 derived lipid mediators [100,101].…”
Section: Omega 3 and Inflammation In Ramentioning
confidence: 77%